Utilising Biographical Narrative Interpretive Methods: rich perspectives on union learning journeys and learner motivations. Issue 4 (18th May 2016) - Ross, C.; Moore, S.
Abstract : This article explores the use of Biographical Narrative Interpretive Methods (BNIM) in research on motivations for trade union learning. Our use of BNIM – a new methodological approach for us – was intended to test our own research practice in an effort to get further inside the 'felt world' and 'lived life' of the union learner. We concluded that educational deficit, employability, ways of learning and collectivism motivate union learners and that BNIM, though problematic, exposes a raw subjectivity in union learner agency and motivation which may not be fully invoked in traditional interview approaches, and which is of interest methodologically to multiple research fields including industrial relations. Whilst we have concerns that BNIM may privilege subjectivity and obscure social locations, we also find that semi-structured interviews may prompt learners to adopt hegemonic frameworks, whereas BNIM can allow the articulation of wider social relationships, desires and counter-hegemonic impulses.